2007
DOI: 10.1007/s10735-007-9152-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases-2 and -9 and RECK during alveolar bone regeneration in rat

Abstract: MMPs are endopeptidases that play a pivotal role in ECM turnover. RECK is a single membrane-anchored MMP-regulator. Here, we evaluated the temporal and spatial expression of MMP-2, MMP-9, and RECK during alveolar bone regeneration. The maxillary central incisor of Wistar rats was extracted and the animals were killed at 1, 3, 7, 10, 14, 21, 28, and 42 days post-operatively (n = 3/period). The hemimaxillae were collected, demineralized and embedded in paraffin. Immunohistochemical analysis was performed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
2
21
0
3
Order By: Relevance
“…On the other hand, a novel endogenous inhibitor of MMPs has been discovered (Sasahara et al 1999a(Sasahara et al , 1999b(Sasahara et al , 2002; products of the RECK gene (reversion-inducing-cysteine-rich protein with Kazal motifs) were first identified by inducing phenotype reversion in mice fibroblasts (NIH-3T3) transformed by Ras (v-KiRas). Current work has revealed that RECK is widely expressed in normal human and mouse tissues (Nuttall et al 2004;Takahashi et al 1998;Accorsi-Mendonça et al 2008;Zambuzzi et al 2009a;Paiva et al 2009). Thus, a temporal and spatial distribution of RECK and other MMPs occurs during remodeling, reorientation, and fusion of mice palate shelves.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a novel endogenous inhibitor of MMPs has been discovered (Sasahara et al 1999a(Sasahara et al , 1999b(Sasahara et al , 2002; products of the RECK gene (reversion-inducing-cysteine-rich protein with Kazal motifs) were first identified by inducing phenotype reversion in mice fibroblasts (NIH-3T3) transformed by Ras (v-KiRas). Current work has revealed that RECK is widely expressed in normal human and mouse tissues (Nuttall et al 2004;Takahashi et al 1998;Accorsi-Mendonça et al 2008;Zambuzzi et al 2009a;Paiva et al 2009). Thus, a temporal and spatial distribution of RECK and other MMPs occurs during remodeling, reorientation, and fusion of mice palate shelves.…”
Section: Introductionmentioning
confidence: 99%
“…found in dentine (Satoyoshi et al 2001;Goldberg et al 2003;Palosaari et al 2003;van Strijp et al 2003) and bone (Maruya et al 2003;César Neto et al 2004;Accorsi-Mendonça et al 2008). MMP-2 is probably one of the proteinases whose activity might be preserved to some extend even using paraformaldehydebased fixatives, because this proteinase has been shown to be resistant to harsh conditions: for example, extracted teeth still showed MMP-2 activity after complete acid demineralization of the dentine in the absence of a fixative (Mazzoni et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, bovine bones were dissected out and gently washed to eliminate blood, fat and other organic impurities. Thereafter, the bones were chemically treated with sodium hydroxide and organic solvents (Zambuzzi et al 2005, 2006; Accorsi‐Mendonça et al 2008a, 2008b) and shaped as shown in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%